An Educational Example: Hanns Eisler’s Das Vorbild Revisited - Bree, Alyssa (Danish Yearbook of Musicology, 2021)
Situating Hanns Eisler’s Das Vorbild within the contexts of the 1952 Festtage zeitgenössischer Musik and his educational impulse presents a starkly different interpretation of the work and its legacy. The debates that occurred between the Stakuko and the VDK – and within each organization – reveal (in)congruencies in the interpretation of socialist realism. These shared goals for socialist realism provide a lens through which Das Vorbild can be understood as exemplifying socialist-realist compositional practice. Yet, his ideas on educating listeners through music is found throughout his career. Das Vorbild and its contexts provide a more refined conception of the overlap between his compositional – and pedagogical – methods and ideas.